Globalization between the Cold War and neo-imperialism - Lehmann, Jennifer M., 1956-; Dahms, Harry F. (Amsterdam ; Oxford : Elsevier JAI, 2006)
This work contains an Introduction by Harry F. Dahms. It includes contents such as: Periodizing Globalization: From Cold War Modernization to the Bush Doctrine Robert J. Antonio and Alessandro Bonanno; Recognizing Empire: Alienation, Authority, and Delusions of Grandeur David Norman Smith; Corporate Warriors: Changing Forms of Private Armed Force in America Harry W. Isaac and Daniel M. Harrison; From Exceptionalism to Imperialism: Culture, Character and American Foreign Policy Lauren Langman and Meghan Burke; 9.11.01 and Its Global Aftermath: Empire Strikes Back? Timothy Luke. It also includes commentaries - Globalization and Social Justice: Working the Tensions of the Dialectics of National Character Karen Monkman; Neoliberalism and its Discontents: Comments on Three Views of the American Empire Barney Warf. It includes five chapters and two commentaries from some of the most respected personalities in the field. It takes a broad and diverse look at the development of globalization.
Includes bibliographical references.
Description based on print version record.
Keywords: Globalization -- Political aspects; Globalization -- Social aspects; Globalization; Social Science -- Sociology -- General; United States -- Foreign relations -- 1989-